Le sentiment d’appartenance dans North and South d’Elizabeth Gaskell - Benjamine Toussaint-Thiriet (Cahiers Victoriens et Edouardiens)
The sense of belonging is one of the major themes of North and South. Margaret Hale, the heroine, has to leave the rural South, to which she feels her heart truly belongs, twice : first as a child, to be brought up by her aunt in London, and then, as a young woman when she must follow her parents and settle in Milton, an industrial town in the North of England. The opposition between her beloved South and this new home is no less striking from a social and cultural point of view than it is from a geographical one. Margaret finds it very difficult at first to adapt to this new environment and the dialogues between her and a local Captain of Industry named John Thornton only serve to underline the—apparently unbridgeable—gap between these two worlds. However, both characters will learn to appreciate the respective values of the world they first rejected. In a similar way, John Thornton and Nicholas Higgins will learn that social gaps are not unbridgeable either, as long as one understands that one’s sense of belonging to a social class need not lead to antagonism. Finally, it is important that people should understand that they are all mutually dependent but that it does not give them the right to try to control others : it is right to feel that you belong to others but not to think that others belong to you. Thus, the sense of belonging—be it from a geographical, social or emotional point of view—can in fact be considered as a moral touchstone.